NOACs for treatment of venous thromboembolism in clinical practice - Schulman, Sam; Singer, Daniel; Ageno, Walter; Casella, Ivan B.; Desch, Marc; Goldhaber, Samuel Z. (Thrombosis and Haemostasis, 2017)
Randomised controlled trials have provided important information on the efficacy and safety of the non-vitamin K antagonist oral anticoagulants (NOACs) for treatment of venous thromboembolism (VTE), leading to registration and increasing use in clinical practice. Many questions remain to be answered, and observational studies are often more suitable for answering “real-world” questions than randomised controlled trials. Patient satisfaction, quality of life, and adherence and persistence in clinical practice with the drug regimen can only be assessed with an open-label design. Evaluation of risk for long-term sequelae of the disease requires much longer follow-up than is possible in registration trials. Treatment patterns and utilisation of health care resources can be assessed from observations in the clinical practice setting. We will review published as well as currently active observational studies with NOACs in VTE, with or without a comparator anticoagulant. These studies are based on cohorts of different sizes, registries, or administrative health care databases. We will also discuss some limitations in analysis and interpretation of observational studies.
Keywords: Venous thromboembolism; non-vitamin K oral anticoagulants; observational studies; recurrence; bleeding; adherence